FISH mapping of 35S and 5S rRNA genes in Artemisia subgenus Dracunculus (Asteraceae): changes in number of loci during polyploid evolution and their systematic implications. (24th January 2013) - Pellicer, Jaume; Garcia, Sònia; Vallès, Joan; Kondo, Katsuhiko; Garnatje, Teresa
Abstract : Fluorescence in situ hybridization (FISH) with 35S and 5S rDNA probes was used to characterize cytogenetically representatives of Artemisia subgenus Dracunculus and allied species and to explore their evolution following polyploidization. At the diploid level two rDNA loci were observed in most species belonging to the A. dracunculus complex, a pattern considered to be the ancestral state for diploid Artemisia . In contrast, representative species from the Eurasian grade which belong to the other major lineage of the subgenus had more heterogeneous rDNA profiles, with three to five loci at the diploid level. Divergent patterns of locus evolution were also detected in polyploids, with the number and distribution of rDNA loci broadly fitting the two main diversification lineages in the subgenus. In the polyploid complex of A. dracunculus, the number of rDNA loci was almost proportional to ploidy, although monoploid genome size was shown to decrease with increasing ploidy. However, in polyploids from the Eurasian grade we found a remarkable reduction in the number of rDNA sites, suggesting that these species might have experienced either a complete loss of loci or a significant reduction in the number of repeats following polyploid formation. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 171, 655 –666 .